Organizacija informacija i katalogizacija - Feldvari, Kristina (Organizacija znanja, 2021)
Teaching and learning how to organize information effectively is a complex process both for educators and students. Cataloguing, which is defined as the process of organizing information by making bibliographic records, is the established procedure for achieving the goal mentioned. Learning the process of cataloguing can be difficult for students because they must become familiar with a large amount of new and complex contents. Apart from that, the skill of exceptional cataloguing is being acquired over the years of working in the field. Since according to our syllabi, the sufficient knowledge and skills should be successfully transferred to students through courses that teach information organization and cataloguing, educators have been trying for years to find the best ways to make the process of transferring it to students as successful as possible. The present paper addresses the purpose and the manner of teaching and learning the information organization as well as the importance and place that future information science professionals have in the contemporary online environment. The paper presents the implementation of the practical classes and the teaching of the process of cataloguing through the courses Organizacija informacija (Organisation of Information) and Teorija i praksa organizacije informacija (Theory and Practice of Organisation of Information) at the Department of Information Sciences of the University of Osijek. In agreement with the Institute of Information Sciences IZUM from Maribor, our Department was given access to work in their COBISS library system in the academic year 2019/2020. The system was later used as the only system for the purpose of conducting practical online teaching at the University of Osijek during the COVID-19 pandemic. An additional aim of the paper was therefore to present the results of a survey conducted among undergraduate and graduate students on the experiences and attitudes based on working with COBISS, as well as their opinion on the virtual practical courses on descriptive cataloguing.
Keywords: cataloguing; education of cataloguers; information organization; izobraževanje katalogizatorjev; izobraževanje na daljavo; izobraževanje prek spleta; katalogizacija; online teaching; organizacija informacij